2013
DOI: 10.7326/0003-4819-158-11-201306040-00005
|View full text |Cite|
|
Sign up to set email alerts
|

Blood Tests to Diagnose Fibrosis or Cirrhosis in Patients With Chronic Hepatitis C Virus Infection

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
217
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 316 publications
(233 citation statements)
references
References 194 publications
9
217
4
3
Order By: Relevance
“…When evaluating those studies that performed direct comparisons, the Forns index and APRI showed a very similar performance for both significant fibrosis and cirrhosis [49] . The Fibroindex was originally proposed for diagnosis of HCV-related fibrosis and includes the following variables: platelet count, AST, and gamma globulin [50] .…”
Section: Serum Biomarkersmentioning
confidence: 82%
See 4 more Smart Citations
“…When evaluating those studies that performed direct comparisons, the Forns index and APRI showed a very similar performance for both significant fibrosis and cirrhosis [49] . The Fibroindex was originally proposed for diagnosis of HCV-related fibrosis and includes the following variables: platelet count, AST, and gamma globulin [50] .…”
Section: Serum Biomarkersmentioning
confidence: 82%
“…Fibro index was also correlated significantly with variation in fibrosis stage when a subset of 30 patients who had undergone a liver biopsy twice was evaluated [50] . Nevertheless, in the mentioned systematic review, the median AUROC for significant fibrosis detection was 0.76 and for cirrhosis was 0.86 [49] . Direct comparisons showed no superiority of Fibroindex over APRI for both significant fibrosis and cirrhosis detection [49] .…”
Section: Serum Biomarkersmentioning
confidence: 94%
See 3 more Smart Citations